2018
DOI: 10.1038/s41598-018-29727-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and lipidomic profile in men with obstructive sleep apnoea: implications for diagnosis and biomarkers of cardiovascular risk

Abstract: The use of metabolomic and lipidomic strategies for selecting potential biomarkers for obstructive sleep apnoea (OSA) has been little explored. We examined adult male patients with OSA (defined by an apnoea-hypopnoea index ≥15 events/hour), as well as age-, gender-, and fat-composition-matched volunteers without OSA. All subjects were subjected to clinical evaluation, sleep questionnaires for detecting the risk of OSA (Berlin and NoSAS score), metabolomic analysis by gas chromatography coupled to mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 52 publications
(54 reference statements)
6
38
0
2
Order By: Relevance
“…They were also linked to promoting fatty acid-induced insulin resistance. In line with our data, Lebkuchen et al showed that species of LPC were upregulated by OSA [ 59 ]. This finding could possibly show a different pattern of expression of LPCs or could be due to one of the main limitations of this study, which is the limited number of participants dictated by the nature of our study, which involved surgical intervention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They were also linked to promoting fatty acid-induced insulin resistance. In line with our data, Lebkuchen et al showed that species of LPC were upregulated by OSA [ 59 ]. This finding could possibly show a different pattern of expression of LPCs or could be due to one of the main limitations of this study, which is the limited number of participants dictated by the nature of our study, which involved surgical intervention.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, two PCs were increased following the surgical treatment of OSA. Previously, Lebkuchen et al showed that people with OSA had a reduction in PCs [ 59 ]. They linked the observed reduction in PCs to the increased damaging activity of various phospholipase A1 (PLA1), A2 (PLA2), and C (PLC), which are activated under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To better define the appropriate treatment for a single patient, we need combinations of biomarkers that are able to characterise IH consequences at the level of the different metabolic organs. Metabolomic and lipidomic profiles in OSA have been reported as distinct from a control group matched for age, BMI and body composition [70]. Also, in a relatively large sample of nonobese and obese OSA, we recently found an independent correlation of OSA severity with the M1 macrophage inflammatory marker sCD163 [23].…”
Section: Adipose Tissue and Ih: Insight From Rodent And Reductionist mentioning
confidence: 68%
“…Overall, metabolites related to lipid-metabolism represented a significant fraction of reported biomarkers, comprising mainly lipids or related biomarkers. Those biomarkers included phospholipids (phosphatidylcholines, posphatidylserines, lysophosphatidylcholines, lysophosphatidic acid, phosphatidylethanolamine, sphingomyelins) [ 41 , 56 ] and circulating endocannabinoids [ 57 ]. Furthermore, differences in urine metabolome were observed, including changes in acylcarnitines, glycerophospholipids and sphingomyelins [ 58 ].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%